Numerical investigation of the separation performance of full-scale AP1000 steam-water separator. (January 2018) - Zhao, Fulong; Zhao, Chenru; Bo, Hanliang
Highlights: Full-scale three-dimension modeling and simulation are conducted using the Euler-Lagrange approach to investigate the steam-water separation performance of the AP1000 separator. The details of steam-water separation efficiency and pressure drop are obtained in the gravity separation space, primary separator and secondary separator under various operating conditions. The head cover and diffuser assembly structure into the upper of the primary separator can greatly increase the steam-water separation efficiency. The inlet velocity distribution of the secondary separator can affect the separation efficiency with ±9% discrepancy compared to the uniform inlet distribution. Abstract: The steam-water separator is a crucial equipment supplying high-quality steam for the turbines in the AP1000 nuclear power station. It is comprised of the gravity separation space, primary separator (swirl-vane separator), secondary separator (wave-type vanes separator) and auxiliary equipment. In the present study, full-scale three-dimension modeling and simulation are conducted using the Euler-Lagrange approach based on the AP1000 steam generator design drawing to investigate the steam-water separating mechanism and the separation performance of the AP1000 separator. The details of steam-water separation efficiency and pressure drop are obtained in the gravity separation space, primary separator and secondary separator under various operating conditions. The numerical results indicate that the separation efficiency increases rapidly as the steam velocity increases and the relative humidity at the outlet of the AP1000 steam-water separator is less than 0.1% which satisfies the design standard of the AP1000 power station. In addition, the head cover and diffuser assembly structure into the upper of the primary separator greatly increases the steam-water separation efficiency though the pressure drop increases somehow as well, compared to the geometric model without head cover and diffuser assembly. Finally, the inlet velocity distribution of the secondary separator, resulting from the arrangement of the orifice plate in front of the secondary separator, affects the separation efficiency with ±9% discrepancy compared to the uniform inlet distribution.